Pulmonary Artery Stump Thrombosis: To Treat or Not to Treat? The Question Is Still Open. Description of a Case and Review of the Literature - Mirijello, Antonio; Santoliquido, Mariateresa; Piscitelli, Pamela; Borelli, Cristina; Serviddio, Gaetano; Simeone, Anna; Grandone, Elvira; De Cosmo, Salvatore (Frontiers in Cardiovascular Medicine, 2021)
Pulmonary artery stump thrombosis (PAST) represents a possible complication after lung surgery. We report the case of a 59-year-old man who presented with dyspnoea about four years after right pneumonectomy due to squamous cell lung cancer. A CT-scan showed the presence of pulmonary artery stump thrombosis. Although there was no evidence of pulmonary embolism, given the clinical features and radiological shape of the thrombus, anticoagulation treatment with low-molecular-weight heparin was started with improvement of symptoms. The patient was discharged on anticoagulant treatment and a pulmonary CT-scan performed 4 months later showed an almost complete resolution of the PAST. Pathophysiological mechanisms of PAST are still unknown, although several hypotheses have been proposed. However, the decision to treat PAST with anticoagulants is still controversial. A review of literature will be provided in order to discuss risk factors, possible aetiologies and to highlight clinical and radiological characteristics that could suggest to treat this condition, in particular when there is an increased risk of complications.